Targeted massively parallel sequencing of candidate regions on chromosome 22q predisposing to multiple schwannomas: An analysis of 51 individuals in a single‐center experience. Issue 1 (15th November 2021) - Piotrowski, Arkadiusz; Koczkowska, Magdalena; Poplawski, Andrzej B.; Bartoszewski, Rafał; Króliczewski, Jarosław; Mieczkowska, Alina; Gomes, Alicia; Crowley, Michael R.; Crossman, David K.; Chen, Yunjia; Lao, Ping; Serra, Eduard; et al.
Abstract: Constitutional LZTR1 or SMARCB1 pathogenic variants (PVs) have been found in ∼86% of familial and ∼40% of sporadic schwannomatosis cases. Hence, we performed massively parallel sequencing of the entire LZTR1, SMARCB1, and NF2 genomic loci in 35 individuals with schwannomas negative for constitutional first‐hit PVs in the LZTR1/SMARCB1/NF2 coding sequences; however, with 22q deletion and/or a different NF2 PV in each tumor, including six cases with only one tumor available. Furthermore, we verified whether any other LZTR1/SMARCB1/NF2 (likely) PVs could be found in 16 cases carrying a SMARCB1 constitutional variant in the 3′‐untranslated region (3′‐UTR) c.*17C>T, c.*70C>T, or c.*82C>T. As no additional variants were found, functional studies were performed to clarify the effect of these 3′‐UTR variants on the transcript. The 3′‐UTR variants c.*17C>T and c.*82C>T showed pathogenicity by negatively affecting the  SMARCB1 transcript level. Two novel deep intronic SMARCB1 variants, c.500+883T>G and c.500+887G>A, resulting in out‐of‐frame missplicing of intron 4, were identified in two unrelated individuals. Further resequencing of the entire repeat‐masked genomics sequences of chromosome 22q in individuals negative for PVs in the SMARCB1/LZTR1/NF2 coding‐ and noncoding regions revealed five potential schwannomatosis‐predisposing candidate genes, that is,   MYO18B, NEFH, SGSM1, SGSM3, and SBF1, pending further verification.